(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Pla-som and pla-chom are Thai traditional fermented fish, which is produced from fish, sugar, salt and roasted rice and is fermented with natural lactic acid bacteria, therefore pathogenic bacteria isolation from these traditional products are sparely reported. This study was aimed to evaluate contamination of pathogenic bacteria and their antibiotic susceptibility from pla-som (n = 15) and pla-chom (n = 15). According from colony, Gram s staining and biochemical characteristics, pathogenic bacteria were isolated and identified; tested for antibiotic susceptibility. Pathogenic bacteria isolate from pla-som (n = 32) were higher rather than pla-chom (n = 12). Suspected pathogenic bacteria were Staphylococcus aureus and Escherichia coli isolated from both of rice-fermented fishes while Salmonella typhimurium, Listeria monocytogenes and K. pneumoniae were commonly contaminated in pla-som. Salt-tolerate pathogens including Vibrio sp. and Aeromonas hydrophila were also identified. Fifty and twenty of pathogenic bacteria were isolated from pla-som and pla-chom, which were determined on susceptibility with fifteen antibiotic discs. Some of pathogenic bacteria were resisted to three or more antibiotics and defined as multidrug resistance (MDR) bacteria. Various pathogenic bacteria including S. aureus, E. coli, K. pneumoniae, S. typhimurium, A. hydrophila, Vibrio sp. and Proteus sp., were antibiotic resistance. Vibrio sp. and A. hydrophila were MDR bacteria with five or more antibiotic resistances. The finding is notified on awareness of recipe in consumers and regarding on food safety of traditional fermentation process in local manufacturers.